Comparative evaluation of the effects of multiple autoclaving on cyclic fatigue resistance of three different rotary Ni-Ti instruments: An in vitro study - Sundaram, Kanthimathinathan Meenakshi (Medknow Publications & Media Pvt Ltd, 2013)
AIMS: The aim of this in vitro study was to evaluate comparatively the effects of multiple autoclaving on surface topography and cyclic fatigue of three different rotary nickel-titanium (Ni-Ti) instruments. MATERIALS AND METHODS: Twenty-one files each of Twisted Files (TF), Revo-S, and RaCe were used in this study. They were grouped as group 1-TF, group 2-Revo-S, and group 3-RaCe. All the files were autoclaved and subjected for scanning electron microscopic analysis and cyclic fatigue analysis. RESULTS: Data were subjected to statistical analysis using one way analysis of variance (ANOVA) and post hoc Tukey's Kramer multiple comparison test. TF exhibited the highest cyclic fatigue resistance followed by Revo-S and RaCe. Scanning electron photomicrographs showed no obvious surface changes in the files after three autoclaving cycles. CONCLUSIONS: Within the limitation of this study, it can be concluded that Twisted Files was the most fatigue resistant compared to Revo-S and RaCe, and multiple autoclaving cycles did not have any significant alterations in the cyclic fatigue resistance of rotary Ni-Ti files.